ICEIT 2024 - 59 Linear Generators: Comparison between Five – Phase and Three – Phase machines - Aslan Sa. Jalal (Zanco Journal of Pure and Applied Sciences)
Linear electrical power generation is one of the methods to generate electrical power from linear moving forces with zero unwanted CO and NO emissions. Such power source can be harvested from linear moving systems such as oscillating engines (the so called free – piston engine), sea and ocean tides and waves. The linear generator is the major part responsible of generating the electrical power from the combined driving linear system and the generator as its load. Such electrical machines are found vastly in three – phase fashion. At first the linear generator in its five – phase mode is modelled, optimised and analysed. Then, the generator mass, cost and running features are investigated and compared with an existing three – phase machine. Few weak points have emerged in the selected five – phase machine models although better operational features have been harvested compared with the base three – phase linear generator model.